2018
DOI: 10.1021/acs.est.8b05630
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Light Absorption Properties of Brown Carbon Emitted from Residential Coal Combustion in China

Abstract: Brown carbon (BrC) fractions, including water-soluble organic carbon (WSOC), water-soluble humic-like substances (HULIS w ), alkaline soluble organic carbon (ASOC), and methanol soluble organic carbon (MSOC) were extracted from particles emitted from the residential combustion of coal with different geological maturities. The abundances and light absorption properties of these BrC fractions were comprehensively studied. The results showed that the abundances of the different constituents of the BrC fraction va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 60 publications
6
76
0
Order By: Relevance
“…2). The measured emission factors in this study fall within the range of previous straw burning experiments (4.7-12.9, 1.2-8.9 and 0.17-1.2 g kg −1 for PM 2.5 , OC and EC, respectively) (Akagi et al, 2011;Hays et al, 2005;Li et al, 2007). The estimated EFs from crop residue burning were generally lower than wood or forest burning emissions (Akagi et al, 2011;Aurell and Gullett, 2013;Jen et al, 2019).…”
Section: Emission Factors Of Carbonaceous Aerosolssupporting
confidence: 81%
See 1 more Smart Citation
“…2). The measured emission factors in this study fall within the range of previous straw burning experiments (4.7-12.9, 1.2-8.9 and 0.17-1.2 g kg −1 for PM 2.5 , OC and EC, respectively) (Akagi et al, 2011;Hays et al, 2005;Li et al, 2007). The estimated EFs from crop residue burning were generally lower than wood or forest burning emissions (Akagi et al, 2011;Aurell and Gullett, 2013;Jen et al, 2019).…”
Section: Emission Factors Of Carbonaceous Aerosolssupporting
confidence: 81%
“…Organic matter (OM), calculated by multiplying OC by 1.3 (Li et al, 2007), was the dominant component of straw burning aerosols, which accounted for ∼ 64 % and ∼ 55 % of the PM 2.5 emitted from corn and wheat burning, respectively (Fig. 2).…”
Section: Emission Factors Of Carbonaceous Aerosolsmentioning
confidence: 99%
“…In addition, results showed that compounds observed in CC aerosols had lower H / C and O / C ratios than those in BB aerosols and vehicle emissions, indicating a higher unsaturated degree and lower oxidation level. There were compounds outside the specified regions, which had a high H / C ratio (≥ 2.2) and DBE of 0, corresponding to saturated oxygenated species, and there could be some long-chain polyalcohols (Lin et al, 2012a).…”
Section: Molecular Composition Detected By Ft-icr Msmentioning
confidence: 99%
“…Moreover, the higher MAE365 in biomass burning and bituminous coal combustion represented a stronger absorbing ability in the case of the MSOC fraction, which reflected greater variation in the chemical composition than in the WSOC fraction. The MAE365 of biomass burning and coal combustion in the WSOC fraction was also higher than that of ambient aerosol and biomass and coal combustion experiments in a laboratory sampling system (Chen et al, 2018;Zhu et al, 2018;Yan et al, 2015;Li et al, 2018;Park and Yu, 2016) ( Figure S4).…”
Section: Emission Characteristics and Optical Properties Of Extractsmentioning
confidence: 90%
“…Purified water was used as a baseline correction before measure. Mass absorption efficiency (MAE, m 2 g -1 C) can be obtained as following equation (Li et al, 2018):…”
Section: Uv−vis Absorption Spectra and Eem Fluorescence Spectramentioning
confidence: 99%